PENGGUNAAN MEDIA SERAT PLASTIK PADA PROSES BIOFILTER TERCELUP UNTUK PENGOLAHAN AIR LIMBAH RUMAH TANGGA NON TOILET - Said, Nusa Idaman (Jurnal Air Indonesia, 2005)
Water pollution in the big cities in Indonesia, especially in DKI Jakarta has shown serious problems. One of the potential sources of water pollution is domestic wastewater that is wastewater from kitchens, laundry, bathing and toilets. These problems have become more serious since the spreads of sewerage systems are still low, so that domestic, institutional and commercial wastewater causes severe water pollution in many rivers or shallow ground water. Based on the fact that the progress of development of sewerage system is still low, it is important to develop low cost technology for individual house hold or semi communal wastewater treatment such as using anaerobic and aerobic submerged biofilter. This paper describes the pilot plan study of individual household wastewater treatment using anaerobic and aerobic submerged biofilter using plastic fiber media. The raw wastewater in this experiment was from household wastewater. Results of experiment shows that under operating condition 12-24 hours hydraulic retention time, the treated water was physically very clear, and according on chemical analysis the removal efficiency of BOD is 73.24 – 94.92 %, COD 65.80 – 90.76 %, total suspended solids (TSS) 95.60 – 97.69 %, and detergent (MBAS) 56.80 – 88.51 %, respectively. Compared to attempt by using charcoal media, the quality of treated water did not show difference significantly. Kata Kunci : Limbah domestik non toilet, biofilter anaerob-aerob, media serat palstik.